The way of living of the inhabitants of the Kazakh Khanate - Muhatova, Orazgul (Balcanica Posnaniensia. Acta et studia, 2013)
<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The Kazakh Khanate appeared in the middle of the 15th century. The political system took its final shape in the 17th century. Kazakh Khans were the descendants of the Genghizids (the descendants of the Genghis khan), who ruled Ak-Orda, Ghirai and Jani Beg. Yet, their power was limited to the Bey Council. The state administration was conducted by <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">sultans, beys <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">and <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">batyrs<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">. Only the descendants of Genghis Khan belonged to the group of sultans. <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Beys <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">and <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">batyrs <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">had to be promoted to achieve their status. There existed a deep social and economic stratification and the subordination of poorer population to the owners of large packs and herds – bays. Shepherding was the main occupation for the Kazakhs.<span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Their way of living was similar to the one of nomadic peoples, which wandered from Central Asia to South-Eastern Europe: the Bulgars, the Pechenegs and the Cumans. The Kazakhs raised mainly sheep, the richer ones also horses and camels, whereas cattle was raised very rarely. Locations for winter pasturing were chosen near rivers, woods and, in general, in the places were animals could find shelter against snowstorm, rainy weather or wind. In the winter, cattle slaughter <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">sogum <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">took place. Spring and autumn pastures were usually located in the steppe in open spaces and the summer ones on the border of the steppe. The sheep and horses were everything for the Kazakhs; they provided food, clothing, shelter (yurts) and household appliances. The land was cultivated to a small extent, most frequently, millet was sown. Only rarely and usually in the winter did the Kazakhs live in homesteads, mainly, clay huts.